Evaluation of anxiety sensitivity, depression, and personality characteristics in chronic subjective dizziness patients - Kantekin, Yunus; Karaaslan, Özgül; Dağıstan, Hakan; Haberal Can, İlknur (Journal of Surgery and Medicine, 2020)
Aim: Dizziness and vertigo are among the most common symptoms in otolaryngology, neurology and psychiatry clinics. In this study, it was aimed to evaluate anxiety sensitivity, depression and personality traits in patients who were followed up with chronic subjective dizziness. Methods: Fifty-one patients with dizziness complaints for at least 3 months and no history of peripheral vestibular disease were enrolled to the patient group, and 51 healthy controls were enrolled to the control group of this case-control study. Anxiety Sensitivity Index-3 (ASI-3), Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI) and Eysenck Personality Questionnaire (EPQ) scale forms were applied to the patient and control groups by a psychiatrist. Results: There was no statistically significant difference in ASI-3 between the groups (P=0.119). In the patient group, the BAI values were found higher than the control group (P<0.001). While BDI values between the patient and control groups were similar, there was a trend for higher depression scores in the patients compared with the healthy individuals (P=0.052). Conclusion: As a result, the presence of anxiety symptoms and neurotic personality characteristics may worsen dizziness development or disease progression. In the treatment of dizziness patients without neurological and otologic problems, a multidisciplinary approach will provide positive contributions to the course of the disease and to the quality of life of the patients.